Sistem Kontrol Suhu Dan Pakan Otomatis Dalam Aquarium Aquascape Menggunakan Nodemcu ESP8266 - firman pradana rachman (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Aquascape is the art of combining aquatic plants, rocks, wood and fish in an aquarium. Temperature is an important part in maintaining fish in an aquarium aquascape. Aquatic plants generally don't do well in hot temperatures. While some types of fish are not very good in cold temperatures. Another problem is how to control fish feed so as not to overdo it. Excess fish feed will increase levels of ammonia (NH3) which is harmful to fish. This research is based on these problems and offers a solution to control the temperature of aquarium water and automatic fish feed based on the Internet of Thing (IoT). This monitoring system uses a nodemcu ESP8266, temperature sensor, fan and automatic fish feed that can be operated via a smartphone. The results of the test show that the temperature control and automatic feed are running well. The use of a 8 cm diameter fan can reduce the water temperature by 2 degrees celsius in 20 minutes.